Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Quantity discrimination, decision-making, and the role of early-life conditions in a lizard - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Christopher R. Friesen; Amelia Y. Peardon; Daniel W. A. Noble (Evolutionary Ecology, 2026)
Quantity discrimination affects a range of behaviours essential for fitness, including social interactions, navigation, and foraging and is widespread across animal taxa. However, in reptiles, evidence for this ability — particularly for small number contrasts — remains limited and mixed. Early-life conditions, such as hormonal exposure and temperature, can also shape brain development and cognitive performance, potentially affecting numerical abilities. Here, we tested the ability of the common garden skink ( Lampropholis guichenoti ) to discriminate between quantities and the effects of elevated prenatal glucocorticoids and incubation temperature on quantity discrimination and decision-making. We assessed quantity discrimination using a spontaneous choice test with food as a stimulus. We subjected lizards to five two-choice tests differing in the number of items (1 VS 4, 1 VS 3, 2 VS 4, 2 VS 3, 3 VS 4) while controlling for total length and area. Contrary to our predictions, lizards did not show clear preferences toward the larger items, providing no evidence of spontaneous quantity discrimination in L. guichenoti . Furthermore, prenatal conditions did not influence latency to make a choice, also a proxy for decision-making. Despite these results, further investigation of quantity discrimination in live-prey-feeding reptiles and the impact of early conditions on other taxa remains an important area of research.

Geoarchaeology at La Sima Cave. A multi-analysis approach to the Middle Paleolithic during MIS 3 in southern Iberia - J.A. Caro-Gómez; C. Borja-Barrera; E.J. Medina-Luque; M. Cañete-Gómez; G. Álvarez-García; F. Díaz del Olmo; J.M. Recio-Espejo; J.A. Riquelme-Cantal; A. Ruiz-Expósito; J.M. Garrido-Anguita (Quaternary International, 2026)

Early environmental conditions do not impact behavioural flexibility in an invasive and noninvasive lizard species - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Kristoffer H. Wild; Christopher R. Friesen; Basile Mauclaire; Amelia Y. Peardon; Daniel W.A. Noble (Animal Behaviour, 2025)

Cyclosporin A-loaded dissolving microneedles for dermatitis therapy: Development, characterisation and efficacy in a delayed-type hypersensitivity in vivo model - Miquel Martínez-Navarrete; Antonio José Guillot; Maria C. Lobita; María Carmen Recio; Rosa Giner; Juan Aparicio-Blanco; María Carmen Montesinos; Hélder A. Santos; Ana Melero (Drug Delivery and Translational Research, 2024)
Several drugs can be used for treating inflammatory skin pathologies like dermatitis and psoriasis. However, for the management of chronic and long-term cases, topical administration is preferred over oral delivery since it prevents certain issues due to systemic side effects from occurring. Cyclosporin A (CsA) has been used for this purpose; however, its high molecular weight (1202 Da) restricts the diffusion through the skin structure. Here, we developed a nano-in-micro device combining lipid vesicles (LVs) and dissolving microneedle array patches (DMAPs) for targeted skin delivery. CsA-LVs allowed the effective incorporation of CsA in the hydrophilic DMAP matrix despite the hydrophobicity of the drug. Polymeric matrix composed of poly (vinyl alcohol) (5% w/v), poly (vinyl pyrrolidine) (15% w/v) and CsA-LV dispersion (10% v/v) led to the formation of CsA-LVs@DMAPs with adequate mechanical properties to penetrate the stratum corneum barrier. The safety and biocompatibility were ensured in an in vitro viability test using HaCaT keratinocytes and L929 fibroblast cell lines. Ex vivo permeability studies in a Franz-diffusion cell setup showed effective drug retention in the skin structure. Finally, CsA-LVs@DMAPs were challenged in an in vivo murine model of delayed-type hypersensitivity to corroborate their potential to ameliorate skin inflammatory conditions. Different findings like photon emission reduction in bioluminescence study, normalisation of histological damage and decrease of inflammatory cytokines point out the effectivity of CsA-LVs@DMAPs to treat these conditions. Overall, our study demonstrates that CsA-LVs@DMAPs can downregulate the skin inflammatory environment which paves the way for their clinical translation and their use as an alternative to corticosteroid-based therapies. Graphical Abstract

Adopting duplex sequencing technology for genetic toxicity testing: A proof-of-concept mutagenesis experiment with N-ethyl-N-nitrosourea (ENU)-exposed rats - Stephanie L. Smith-Roe; Cheryl A. Hobbs; Victoria Hull; J. Todd Auman; Leslie Recio; Michael A. Streicker; Miriam V. Rivas; Gabriel A. Pratt; Fang Yin Lo; Jacob E. Higgins; Elizabeth K. Schmidt; Lindsey N. Williams; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Distal fluvial to lacustrine/palustrine carbonate facies of the El-Ris Formation (Late Miocene?) at the Bahariya Depression, Western Desert, Egypt: Depositional model and controls - H.A. Wanas; I. Armenteros; C. Recio; E.S. Sallam; C.E. Nieto (Journal of African Earth Sciences, 2023)

A comprehensive review of nitrogen removal in an electro-membrane bioreactor (EMBR) for sustainable wastewater treatment - A. C. Sorgato; T. C. Jeremias; M. Á. Lobo-Recio; F. R. Lapolli (International Journal of Environmental Science and Technology, 2023)

Error-corrected duplex sequencing enables direct detection and quantification of mutations in human TK6 cells with strong inter-laboratory consistency - Eunnara Cho; Carol D. Swartz; Andrew Williams; Miriam V. Rivas; Leslie Recio; Kristine L. Witt; Elizabeth K. Schmidt; Jeffry Yaplee; Thomas H. Smith; Phu Van; Fang Yin Lo; Charles C. Valentine; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Effects of bisphenol F, bisphenol S, and bisphenol AF on cultured human osteoblasts - E. García-Recio; V. J. Costela-Ruiz; L. Melguizo-Rodríguez; J. Ramos-Torrecillas; R. Illescas-Montes; E. De Luna-Bertos; C. Ruiz (Archives of Toxicology, 2023)
Bisphenol A (BPA) analogs, like BPA, could have adverse effects on human health including bone health. The aim was to determine the effect of BPF, BPS and BPAF on the growth and differentiation of cultured human osteoblasts. Osteoblasts primary culture from bone chips harvested during routine dental work and treated with BPF, BPS, or BPAF for 24 h at doses of 10 –5 , 10 –6 , and 10 –7 M. Next, cell proliferation was studied, apoptosis induction, and alkaline phosphatase (ALP) activity. In addition, mineralization was evaluated at 7, 14, and 21 days of cell culture in an osteogenic medium supplemented with BP analog at the studied doses. BPS treatment inhibited proliferation in a dose-dependent manner at all three doses by inducing apoptosis; BPF exerted a significant inhibitory effect on cell proliferation at the highest dose alone by an increase of apoptosis; while BPAF had no effect on proliferation or cell viability. Cell differentiation was adversely affected by treatment with BPA analogs in a dose-dependent, observing a reduction in calcium nodule formation at 21 days. According to the results obtained, these BPA analogs could potentially pose a threat to bone health, depending on their concentration in the organism.

Invited review: Novel methods and perspectives for modulating the rumen microbiome through selective breeding as a means to improve complex traits: Implications for methane emissions in cattle - O. González-Recio; M. Martínez-Álvaro; Francesco Tiezzi; A. Saborío-Montero; C. Maltecca; R. Roehe (Livestock Science, 2023)

Geology, geochemistry, isotope geochemistry and fluid inclusions of the Early Carboniferous granitic rocks from Bajo de La Leona, Deseado Massif (Santa Cruz, Argentina) and geological relationships with the Triassic-Jurassic magmatism - R.E. de Barrio; C. Recio; F.J. Ríos; A.P. Rolando; M.A. Del Blanco; I.B. Schalamuk (Journal of South American Earth Sciences, 2023)

The Faja Eruptiva of the Eastern Puna and the Sierra de Calalaste, NW Argentina: U–Pb zircon chronology of the early Famatinan orogeny - C. Casquet; P. Alasino; C. Galindo; R. Pankhurst; J. Dahlquist; E. G. Baldo; C. Ramacciotti; S. Verdecchia; M. Larrovere; C. W. Rapela; C. Recio (Journal of Iberian Geology, 2021)

Can dynamic in vitro digestion systems mimic the physiological reality? - D. Dupont; M. Alric; S. Blanquet-Diot; G. Bornhorst; C. Cueva; A. Deglaire; S. Denis; M. Ferrua; R. Havenaar; J. Lelieveld; A. R. Mackie; M. Marzorati; et al. (Critical Reviews in Food Science and Nutrition, 2019)

A glycine transporter SLC6A5 frameshift mutation causes startle disease in Spanish greyhounds - Sarah C. Murphy; Alfredo Recio; Cristian de la Fuente; Ling T. Guo; G. Diane Shelton; Leigh Anne Clark (Human Genetics, 2019)

Molecular topology: a strategy to identify novel compounds against ulcerative colitis - María Gálvez-Llompart; Maria C. Recio; Ramón García-Domenech; Jorge Gálvez (Molecular Diversity, 2017)

Understanding home range behaviour and resource selection of invasive common brushtail possums (Trichosurus vulpecula) in urban environments - A. L. Adams; M. R. Recio; B. C. Robertson; K. J. M. Dickinson; Y. van Heezik (Biological Invasions, 2013)

Antiviral activity of casein and α s2 casein hydrolysates against the infectious haematopoietic necrosis virus, a rhabdovirus from salmonid fish - S Rodríguez Saint‐Jean; A De las Heras; W Carrillo; I Recio; J B Ortiz‐Delgado; M Ramos; J A Gomez‐Ruiz; C Sarasquete; S I Pérez‐Prieto (Journal of Fish Diseases, 2013)
Salmonid fish viruses, such as infectious haematopoietic necrosis virus ( IHNV ), are responsible for serious losses in the rainbow trout and salmon‐farming industries, and they have been the subject of intense research in the field of aquaculture. Thus, the aim of this work is to study the antiviral effect of milk‐derived proteins as bovine caseins or casein‐derived peptides at different stages during the course of IHNV infection. The results indicate that the 3‐h fraction of casein and α S2 ‐casein hydrolysates reduced the yield of infectious IHNV in a dose‐dependent manner and impaired the production of IHNV ‐specific antigens. Hydrolysates of total casein and α S2 ‐casein target the initial and later stages of viral infection, as demonstrated by the reduction in the infective titre observed throughout multiple stages and cycles. In vivo , more than 50% protection was observed in the casein‐treated fish, and the kidney sections exhibited none of the histopathological characteristics of IHNV infection. The active fractions from casein were identified, as well as one of the individual IHNV ‐inhibiting peptides. Further studies will be required to determine which other peptides possess this activity. These findings provide a basis for future investigations on the efficacy of these compounds in treating other viral diseases in farmed fish and to elucidate the underlying molecular mechanisms of action. However, the present results provide convincing evidence in support of a role for several milk casein fractions as suitable candidates to prevent and treat some fish viral infections.

Topological virtual screening: a way to find new compounds active in ulcerative colitis by inhibiting NF-κB - María Gálvez-Llompart; María C. Recio; Ramón García-Domenech (Molecular Diversity, 2011)

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Trends in grass pollen season in southern Spain - Herminia García-Mozo; C. Galán; P. Alcázar; C. Díaz de la Guardia; D. Nieto-Lugilde; M. Recio; P. Hidalgo; F. Gónzalez-Minero; L. Ruiz; E. Domínguez-Vilches (Aerobiologia, 2010)

High incidence of Aspergillus and Penicillium spores in the atmosphere of the cave of Nerja (Malaga, southern Spain) - S. Docampo; M. M. Trigo; M. Recio; M. Melgar; J. García-Sánchez; M. C. Calderón-Ezquerro; B. Cabezudo (Aerobiologia, 2010)

Geochronological, stable isotopes and fluid inclusion constraints for a premetamorphic development of the intrusive-hosted Björkdal Au deposit, northern Sweden - K. Billström; C. Broman; E. Jonsson; C. Recio; A. J. Boyce; P. Torssander (International Journal of Earth Sciences, 2009)

Identification and relationships of accessions grown in the grapevine (Vitis vinifera L.) Germplasm Bank of Castilla y Léon (Spain) and the varieties authorized in the VQPRD areas of the region by SSR-marker analysis - J. C. Santana; E. Hidalgo; A. I. de Lucas; P. Recio; J. M. Ortiz; J. P. Martín; J. Yuste; C. Arranz; J. A. Rubio (Genetic Resources and Crop Evolution, 2008)

Stable isotope composition of F-Pb-Zn mineralization in the Valle de Tena (Spanish Central Pyrenees) - I. Subías; C. Recio; I. Fanlo; C. Fernández-Nieto (Mineralium Deposita, 1997)